Facile Synthesis of Benzo[c]chromen-6-ones via Base-Promoted Reaction of 4-Chloro-3-formylcoumarin and α,α-Dicyanoolefins - Alizadeh, Abdolali; Farajpour, Behnaz (Synlett, 2022)
Herein, a chemoselective protocol for the facile and efficient synthesis of substituted benzo[c]chromen-6-ones is presented. The reaction took place under green and mild conditions with group-assisted purification (GAP) by using inexpensive and readily available precursors.
Keywords: 4-chloro-3-formylcoumarin; α,α-dicyanoolefins; benzo[c]chromen-6-ones; chemoselective reactions; group-assisted purification